Environmental assessment of central solar heating plants with seasonal storage located in Spain. (10th September 2021) - Raluy, Rosa Gemma; Guillén-Lambea, Silvia; Serra, Luis M.; Guadalfajara, Mateo; Lozano, Miguel A.
Abstract: Renewable energies can play a very important role in the development of a new energy model contributing effectively towards a more sustainable development in the mid and long term. In this context Central Solar Heating Plants with Seasonal Storage (CSHPSS) are able to provide space heating and Domestic Hot Water (DHW) to residential buildings with high solar fractions (>50%). These systems are already being used in Central and Northern Europe, as well as in Canada, where there is an important experience in district heating systems. The study presented herein presents an environmental assessment, applying the Life Cycle Assessment (LCA) method, of a CSHPSS, which should cover the space heating and DHW demand of 500 dwellings of 100 m 2, located in Zaragoza, Spain. Environmental burdens through the life cycle of the system are estimated based on greenhouse gas emissions, and comprehensive environmental indicators as the ReCiPe and Cumulative Energy Demand (CED). These indicators allow to evaluate the reduction of the environmental load achieved by the CSHPSS analyzed with respect to conventional space heating and DHW systems, as well as to identify the most critical aspects from the environmental perspective. In this article, the environmental behavior of the CSHPSS is decoupled into the two demands covered, heating and DHW, in order to quantify the environmental impact of each generation system. A detailed life cycle inventory is presented with the aim of promoting the development of increasingly efficient technologies from the environmental point of view, not only in the operation phase but also in the construction of the equipment. Furthermore, an in-depth analysis is performed to evaluate the variation of the environmental impact depending on the climatic conditions. The CSHPSS is also dimensioned in different Spanish cities and a LCA is carried out for nine locations. The results can help different stakeholders to make decisions in order to optimize the renewable energy generation systems taking in account its whole life cycle and to point out the necessity to evaluate the environmental impact essentially in the production phase for all renewable energy systems.